Peran Customer Experience Dalam Memediasi Pengaruh Online Innovation Dan Service Quality Terhadap Repurchase Intention (Studi Pelanggan Grab Bike Di Kota Bandung) - Syafa Tasya Fahira; Yadi Ernawadi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
The purpose of this study was to examine the effect of online innovation and service quality on repurchase intention mediated by the customer experience of Grab Bike customers in the city of Bandung. A total of 120 respondents who have experience using Grab Bike participated in this study. The cross-sectional or one shot method is used to obtain data. The instrument has been declared validity and reliability tests include convergent validity, discriminant validity, and composite reliability. The data analysis technique used is structural equation modeling (SEM) using SmartPLS version 3.0. Of the seven proposed research hypotheses, six are supported by empirical data. With the results of research online innovation and service quality directly and indirectly affect the repurchase intention. The results of this study are expected to provide benefits for subsequent research and the management of the assessed object or similar service industries related to the design of strategies relevant to improving the quality of these attributes. The thing that distinguishes this study from previous research is the addition of service quality as an antecedent of repurchase intention. Researchers are further advised to explore other variables that can mediate the influence of online innovation on repurchase intention. Keywords: Online Innovation, Service Quality, Customer Experience, and Repurchase Intention